A Study of Spectrum of Adipose Tissue Tumours At A Tertiary Care Hospital, Gujarat - Thaker, Mayuri V; Gohil, Mayuri R (Annals of Pathology and Laboratory Medicine, 2018)
INTRODUCTION: Adipose Tissue Tumors(ATT) are the most common benign soft tissue tumors in humans. The actual incidence of Adipose Tissue Tumors is probably higher than reported because of its insidious slow growing pattern and minimal associated symptoms. The purpose of our study is to evaluate pattern of distribution of the adipose tissue tumours in relation to different age groups, sex and anatomical site distribution and frequency of various benign & malignant variants. MATERIAL AND METHOD: The present study has been done in Histopathology section of Pathology Department of Government Medical College & Sir T General Hospital,Bhavnagar for the period of 2 years from 01/01/2013 to 31/12/2015.Total 87 cases were studied. RESULTS: In the present study, adipose tissue tumours constitute 1.33% of total yearly histopathological specimens. The incidence of benign soft tissue tumours is 96.55% and that of malignant tumours is 3.45%. Ratio of benign to malignant ATT is 28:1. Commonest age group for benign tumors was 30-50 years & for malignant lesions above 50 yrs age. Overall incidence of adipose tissue tumors is slightly higher (52.87%) in females in comparison of males (47.13%). The most common benign variant of lipoma is fibrolipoma. CONCLUSION: Present study concludes preponderence of Benign Adipose Tissue Tumours overall and also in females with trunk being a favourable site. Malignant tumours are common in males with lower extremities being the commonest site.